ANALISIS PERBANDINGAN BIAYA DAN RISIKO PEKERJAAN SALURAN BETON BERBENTUK U PRECAST PABRIKAN DAN IN SITU PADA METODE PEMBAYARAN KOMPENSASI PENUH (STUDY KASUS PEKERJAAN SALURAN BETON BERBENTUK U DI KOTA MAGELANG TAHUN 2025) - Santosa Endra Gunawan; Albani Musyafa (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Road drainage channels as complementary road structures in Magelang City in the form of U-shaped concrete channels made using the Factory Precast method and the In Situ method.This study analyzes the work of U-shaped concrete channels using the Factory Precast method and carried out in situ by calculating the Unit Price Analysis of the Work. Price Analysis is calculated based on the Circular Letter of Director General of Construction Development No:68 / SE / Dk / 2024 concerning Procedures for Compiling Cost Estimates for Construction Work in the Public Works and Public Housing Sector.The Unit Price Analysis of Work also refers to the Circular Letter of the Director General of Highways, Ministry of Public Works and Public Housing, Number 16.1/SE/Db/2020 concerning the General Specifications of Highways 2018 for Road and Bridge Construction Works (Revision 2), which stipulates that payment for U-shaped channel work must be paid according to the contract price per unit of measurement for the payment item, where the price and payment must be full compensation.The study also calculated the level of risk for problems that could arise during the implementation of precast U-shaped concrete channel work from manufacturers and in situ.Research data was taken through a survey of material prices and workers' wages, as well as filling out questionnaires by taking samples of respondents from Supervising Consultants and Field Supervisors.The research results show that the price per meter of length of U-shaped concrete channel work with full compensation payment using the In Situ method is cheaper than the Factory Precast method. In the In Situ method, the unit price per meter of length for U-shaped concrete channel work Size 40/60 is Rp. 1,129,889.83 and for size 50/70 is Rp. 1,325,344.70. Meanwhile, in the Precast Factory method, the unit price per meter length for size 40/60 is Rp. 1,443,028.48 and the unit price per meter length for size 50/70 is Rp. 1,617,195.15Based on the research results, although In situ is cheaper than Pre Cast, it has a higher level of risk for potential problems that can arise, namely the quality of the concrete is not in accordance with the specifications, the dimensions of the channels are not in accordance, the work time is long, the finishing of the work is not neat, and the concrete reinforcement steel is not in accordance with the specifications so that stricter supervision is needed so that the results of the construction work are good.